PENGARUH CORPORATE SOCIAL MARKETING DAN GREEN MARKETING TERHADAP GREEN CONSUMERISM BEHAVIOR PADA AROMA SPA SANUR DENPASAR - Damayanti, Dewa Ayu Rara; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen, 2016)
The importance of preserving the current environment, should encourage individuals to consume products that are environmentally friendly. Aroma Spa is one of Bali's famous Spa which adopts the theme of eco-friendly lifestyle. The purpose of this study was to determine the influence of corporate social marketing and green marketing strategies to green consumerism behavior at Aroma Spa, Sanur Denpasar. This research was conducted at the Aroma Spa, Sanur Denpasar engaged in the field of body care services with multiple linear regression analysis techniques. The number of samples, namely by using purposive sampling method is as much as 102 respondents. Based on the results of the analysis showed that corporate social marketing and green marketing strategies and significant positive effect simultaneously to green consumerism behavior at Aroma Spa, Sanur Denpasar. Corporate social marketing and green marketing strategies and significant positive effect partially to green consumerism behavior at Aroma Spa, Sanur Denpasar.
Keywords: corporate social marketing; strategi green marketing; green consumerism behavior